Vivências do dia-a-dia de pais com filhos deficientes - Martins, MM (2014)
The family is a space for learning that is in constant renewal and enrichment. However, when one of its members has a disability, the family plays a major role in the daily reconstruction of the intimate and social life of its members. And as ageing is inevitable, parents are constantly worried about who will take care of their children. Children become increasingly more dependent as parents face physical limitations in caring for their children. A qualitative descriptive exploratory study using a phenomenological approach was carried out to answer the initial question: “Do parents of adult children with disabilities experience specific needs?” Based on this methodology, data were collected through semi-structured interviews with five elderly parents caring for their disabled children and attending the CEFPI (Centre for Integrated Vocational Education and Training). Results indicate that these parents live for their children, which is inherent to a moderate level of care dependence for self-care functions such as personal hygiene, walking, dressing and undressing. They care for the children by themselves, and they feel alone in their role.